'Education is a cultivating and nurturing experience'. (2nd February 2019) - Willis, Richard
Abstract : John Dewey's educational philosophy rejected learning by rote and the narrow physical boundaries of school itself. His ideas of progressive education embraced the wider community and real-life tasks.